Effects of Different Processing Conditions on Physicochemical Properties, Bioactive Compounds and Sensory Acceptance of Betel Nut Tea - Singkhum, Unchalin (วารสารผลิตกรรมการเกษตร, 2022)
The effects of various roasting-rolling temperatures (40-50, 50-60, 70-80 °C), rolling times (10, 15, 20 minutes), and drying temperatures (60 and 80 °C) on water activity (aw), color values (L*, a*, b*), total phenolic content, antioxidant activity by DPPH, and ferric ion reducing antioxidant power (FRAP) in Betel nut tea were studied. The total phenolic content and antioxidant activity decreased when the roasting-rolling and drying temperatures increased (p≤0.05). As a result, the tea processing condition that produced the most bioactive compounds (roasting-rolling temperature of 50-60 °C, 15 minutes of rolling time, and drying temperature of 60 °C for 3 hours) was chosen to investigate the amount of water (60 and 80 milliliters) and water temperature (80, 90, and 100 °C) needed to make tea. The water and the water temperature did not affect the bioactive compounds (p>0.05). Sensory evaluation with 50 panelists using a 9-point hedonic scale showed differences in preference scores in the taste (p≤0.05), but there was no significant difference in terms of color, odor, and overall liking for Betel nut tea (p>0.05). Thus, the appropriate formula for Betel nut tea making was 5 grams of tea, 60-80 milliliters of water, and 80-90 °C water temperature.